Development And Characterization Of Chitosan-Cellulose Nanofiber Hydrogel Scaffold For Tissue Engineering Application - Ho, Yue Cheng (Universiti Sains Malaysia, 2022)
Chitosan (CS), as a naturally derived hydrogel scaffold which exhibit insufficient mechanical strength, has been proven a major limitation for tissue engineering application such as bone tissue engineering. In this study, the limitation was tackled by incorporation of cellulose nanofiber (CNF) (0%, 5%, 10%, 15%, 20% and 25 WCNF/WCS%) in medium molecular weight (MCS) and high molecular weight CS (HCS) hydrogel scaffold. The Fourier Transform Infrared (FTIR) analysis revealed that the interaction between CNF with both MCS and HCS is physical rather than chemical without altering their chemical structure, which is ideal to maintain the biocompatible characteristic of both CS and CNF. Although without chemical interaction, the reinforcement effect of CNF on MCS and HCS in terms of mechanical properties was proven through texture profile analysis and compression test, in which the incorporation of CNF results in the enhancement of hardness, resilience and compression stress at optimum CNF loading. In case of swelling properties, the incorporation of CNF into CS scaffold cause reduced maximum swelling ratio. The results obtained also revealed that HCS exhibit higher hardness and compression stress compared to that of MCS at any CNF loading. However, the maximum swelling ratio of HCS series is lower as compared to that of MCS.